2001
DOI: 10.1128/jvi.75.2.645-653.2001
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Protective Efficacy of Oligomeric Human Immunodeficiency Virus Type 1 gp140

Abstract: The biologically active form of the human immunodeficiency virus type 1 (HIV-1) envelope (Env) glycoprotein is oligomeric. We previously described a soluble HIV-1 IIIB Env protein, gp140, with a stable oligomeric structure composed of uncleaved gp120 linked to the ectodomain of gp41 (P. L. Earl, C. C. Broder, D. Long, S. A. Lee, J. Peterson, S. Chakrabarti, R. W. Doms, and B. Moss, J. Virol. 68:3015-3026, 1994). Here we compared the antibody responses of rabbits to gp120 and gp140 that had been produced and pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(100 citation statements)
references
References 82 publications
2
98
0
Order By: Relevance
“…It is possible that immunizing with an immunogen with better CD4-binding properties would result in more potent VHH. Previous studies have shown that purified trimeric envelope proteins are somewhat better at eliciting cross-subtype-neutralizing antibodies than monomeric recombinant gp120 (6,7,22,32,38,90). We are currently screening llamas immunized with recombinant trimeric gp140.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that immunizing with an immunogen with better CD4-binding properties would result in more potent VHH. Previous studies have shown that purified trimeric envelope proteins are somewhat better at eliciting cross-subtype-neutralizing antibodies than monomeric recombinant gp120 (6,7,22,32,38,90). We are currently screening llamas immunized with recombinant trimeric gp140.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we anticipated that antibodies to these VACV proteins would cross react with the MPXV homologs and provide at least partial protection. We chose to use QS-21, based on our previous experience with recombinant HIV proteins in a monkey model [62], even though we had not yet determined the superiority of this adjuvant for inducing VACV protection in mice. The recombinant VACV proteins were immunogenic in monkeys and binding antibodies were detected after the first immunization and boosted by a second, at which time VACV neutralizing and comet-reducing antibodies were also found.…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches have been tried with reasonable success. 88,[155][156][157][158][159][160][161][162][163][164][165][166] Yang and colleagues used GCN4-stabilized oligomers to demonstrate that antibodies induced by oligomeric gp140 were more effective at neutralizing heterologous primary isolates, compared to antibodies elicited by the corresponding monomeric gp120 protein. 167 Earl and colleagues made similar observations in rhesus macaques using a trimeric Env protein from SIV.…”
Section: Structural Optimization To Target Conserved Neutralization Ementioning
confidence: 99%